ANALISIS MOTIVASI BELAJAR BAHASA MANDARIN SISWA KELAS X JURUSAN PARIWISATA SMK N 1 KETAPANG - Fitri Sudaiyani; Lily Thamrin; Bun Yan Khiong (Universitas Tanjungpura, 2019)
AbstractIn learning foreign languages, learning motivation has a very important role and can encourage students in the learning process. Factors of motivation to learn a foreign language can be divided into internal factors and external factors, which include internal factors, namely: interest and initiative. External factors, namely: the value of achievement, use value and teachers. The author conducted this research to find out what factors influence motivation to learn Mandarin in class X students of the Department of Tourism at SMK N I Ketapang. The results of the study state that there are 55% of class X students of the Department of Tourism at SMK N 1 Ketapang who have strong motivation. Viewed from internal factors, motivation to learn Mandarin students of SMKN I Ketapang is strongly influenced by the “initiative” factor. Seen from external factors, motivation to learn Mandarin students of SMK N I Ketapang students is greatly influenced by the factor of “use values”. At the same time the variable X (achievement value,use values,eachers,interests and initiatives) significantly influence motivation to learn Mandarin in class X in the Department of Tourism at SMK N I Ketapang by 70.7%.Keywords: Learning Motivation , External Motivation, Internal Motivation